2021
DOI: 10.1371/journal.pgen.1009429
|View full text |Cite
|
Sign up to set email alerts
|

A loss-of-function mutation in RORB disrupts saltatorial locomotion in rabbits

Abstract: Saltatorial locomotion is a type of hopping gait that in mammals can be found in rabbits, hares, kangaroos, and some species of rodents. The molecular mechanisms that control and fine-tune the formation of this type of gait are unknown. Here, we take advantage of one strain of domesticated rabbits, the sauteur d’Alfort, that exhibits an abnormal locomotion behavior defined by the loss of the typical jumping that characterizes wild-type rabbits. Strikingly, individuals from this strain frequently adopt a bipeda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…We have also demonstrated that, although the number of Rorb-expressing cells in somatosensory cortex is not dramatically different between mutant and WT mice, the expression of Scnn1a is markedly different, with many fewer cells labeled in mutant mice. We therefore support the finding that, in layer 4 neurons, Rorb is important for cell fate and/or terminal differentiation, similar to what has been reported previously regarding cortical barrels, spinal cord, and retina (KAUTZMANN et al 2011;LIU et al 2013b;FU et al 2014;WANG et al 2014;CLARK et al 2020;CARNEIRO et al 2021). Thus, while Rorb-expressing cells are still present in sensory areas in mutant mice, they may not function normally in cortical circuitry.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We have also demonstrated that, although the number of Rorb-expressing cells in somatosensory cortex is not dramatically different between mutant and WT mice, the expression of Scnn1a is markedly different, with many fewer cells labeled in mutant mice. We therefore support the finding that, in layer 4 neurons, Rorb is important for cell fate and/or terminal differentiation, similar to what has been reported previously regarding cortical barrels, spinal cord, and retina (KAUTZMANN et al 2011;LIU et al 2013b;FU et al 2014;WANG et al 2014;CLARK et al 2020;CARNEIRO et al 2021). Thus, while Rorb-expressing cells are still present in sensory areas in mutant mice, they may not function normally in cortical circuitry.…”
Section: Discussionsupporting
confidence: 92%
“…was recently shown to underlie abnormal gait in sauteur d'Alfort rabbits (CARNEIRO et al 2021). Delayed onset of fertility in male mice with Rorb mutations has also been described previously (ANDRE et al 1998b).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…7A ), with comparable expression between the fovea and parafovea ( Supplementary Material, Table S2 ). Previous studies have shown that retinal RORB expression regulates circadian timing ( 36 ) and is important for neuronal differentiation and patterning ( 37 , 38 ). RORB encodes two isoforms with distinct N-terminal domains.…”
Section: Resultsmentioning
confidence: 99%
“…Efforts to identify the molecular cause of a QTL often implicitly assume that the QTL contains only a single causal variant that can be "fine-mapped" through a series of experiments, aided by annotations of gene function and, more recently, computational predictions of variant effect (Adzhubei et al, 2013;Choi and Chan, 2015;Kircher et al, 2014;Sim et al, 2012). Well-known success stories demonstrate that single causal genes and variants can be identified in QTLs (Carneiro et al, 2021;Sutter et al, 2007;Van Laere et al, 2003).…”
Section: Introductionmentioning
confidence: 99%